Draft Genome Sequence of a Caffeine-Utilizing Bacterium, Cupriavidus sp. Strain D384 - Watahiki, Saori (Genome Announc, 2017)
Cupriavidus sp. D384 was isolated from forest soil in Japan and is known to utilize caffeine as a sole source of carbon and energy. We report here the 6,835,230-bp genome sequence for this strain, which contains 6,116 predicted coding sequences, including gene operon for alkaloid degradation.